Real-Scale Experimental Evaluation of Energy and Thermal Regulation Effects of PCM-Based Mortars in Lightweight Constructions - Manuel Andrés; Filipe Rebelo; Álvaro Corredera; António Figueiredo; José L. Hernández; Víctor M. Ferreira; Luis A. Bujedo; Romeu Vicente; Francisco Morentin; Jesús Samaniego (Applied Sciences, 2022)
Lightweight construction is experiencing a significant market implementation with sustained growth both for new buildings and retrofitting purposes. Despite the acknowledged advantages of this type of construction, their reduced thermal inertia can jeopardize indoor thermal comfort levels while leading to higher energy consumption due to high indoor temperature fluctuations and overheating rates. The incorporation of phase change materials (PCMs) into constructive solutions for lightweight buildings is a promising strategy to guarantee adequate thermal comfort conditions. Particularly, the utilization of mortars embedding PCMs as an indoor wall coating for new and existing buildings represents a solution that has not been widely explored in the past and needs further development and validation efforts. This work pursues the analysis of the thermal regulation effects generated by two thermally-enhanced mortars incorporating microencapsulated PCMs with different operating temperature ranges. To that end, an experimental campaign was conducted in Valladolid (Spain) to address the investigation of the proposed solution under a real-scale relevant environment. The proposed mortars were applied as an indoor coating to the envelope of a single-zone lightweight construction that was monitored (under different weather conditions along 1-year monitoring campaign) together with an identical building unit where the mortar was not added to the constructive base layer. The analysis of indoor temperature fluctuations under free-floating operating mode as well as the energy consumption of HVAC equipment under controlled-temperature operation was specifically targeted. Results derived from the continuous monitoring campaign revealed lower temperature fluctuations during summer and shoulder seasons, reducing indoor temperature peaks by 1–2 °C, and producing a time delay of 1–1.5 h into the temperature wave. A clear reduction in energy use due to the incorporation of the PCM-based indoor coating panels is also observed. Thus, this experimental research contributes to proving that the use of innovative mortars incorporating embedded PCMs enables the development of high-end efficient building solutions with innovative materials towards a sustainable built environment.